2013
DOI: 10.1186/1476-511x-12-43
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of apolipoprotein-E in residents of the European North of Russia

Abstract: BackgroundApolipoprotein-E (apoE) is one of the metabolically active apoproteins and plays an important role in lipid metabolism. However, there are no data on levels of apoE in residents of the North in spite of the fact that specific features of lipid metabolism in the northerners are described. The present work was designed to study plasma levels of apoE in residents of the European North of Russia.MethodsA total of 937 native residents of the European North of Russia (463 men and 474 women) aged 13–60 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
4
6
0
Order By: Relevance
“…In our study, plasma ApoE levels were considered low, but comparable to those found in the study by Kaneva et al, where the shift in plasma ApoE toward lower levels in European residents as a result of specific features of lipid metabolism was demonstrated [ 32 ]. We also demonstrated the screening utility of maternal serum ApoE measurement as a potential noninvasive marker of DS.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, plasma ApoE levels were considered low, but comparable to those found in the study by Kaneva et al, where the shift in plasma ApoE toward lower levels in European residents as a result of specific features of lipid metabolism was demonstrated [ 32 ]. We also demonstrated the screening utility of maternal serum ApoE measurement as a potential noninvasive marker of DS.…”
Section: Discussionsupporting
confidence: 89%
“…Accordingly, diverse studies have shown that Apo E −/− mice suffer hypercholesterolemia and an association between Apo E levels and CVD has also been reported in humans [ 51 , 52 ]. Even more, it has been shown that in the absence of some isoforms of Apo E, the beneficial cardioprotective effect of ω3 PUFA may be partially lost [ 53 , 54 ]. Of note, our results highlight an association between Apo E increase in LDL and an improved TG profile in obese subjects after four weeks intervention with ω3-milk.…”
Section: Discussionmentioning
confidence: 99%
“…Too little apoE impairs the clearance of TG-rich lipoproteins and their remnants from plasma. Too much apoE stimulates very low-density lipoproteins production in the liver and impairs lipoprotein lipase-mediated lipolysis, leading to hypertriglyceridemia [ 43 , 44 ]. We have previously shown that the low apoE levels may contribute to hypertriglyceridemia in residents of the European North of Russia [ 45 ].…”
Section: Discussionmentioning
confidence: 99%